Pengaruh E–Service Quality Dan E–Recovery Terhadap E-Loyalty Pada 150K Optik - Dea Putri Novita Parinduri; Sarwo Edi (Universitas Labuhanbatu, 2022)
E-Service Quality and E-Recovery Service Quality against e-loyalty on 150K optics. This study uses quantitative methods. The sampling method is purposive sampling technique aimed at 150K optical consumers in Medan City by distributing questionnaires to 70 respondents. The results of this study partially and simultanmenemukan that E – service Quality and E-Recovery Service Quality work positively significant to e-Loyalty at 150K optics.